Method Research on Data Assimilation for Burnup Distribution of PWR Based on Three=dimensional Variation and Neutral Network Algorithm - GUO Lin;WAN Chenghui;LI Yunzhao;WU Hongchun (Yuanzineng kexue jishu, 2022)
In this paper, a data-assimilation method-was proposed and applied for the burnup distribution of PWR. The burnup distribution is significant to the safety and economy of the reactor, as it is essential for the fuelreloading design and optimization. Due to the burnup distribution can’t be measured directly during the reactor operation, the numerical simulation is widely applied in reactor engineering. However, there are definitely exist differences between the physical model by the numerical simulation and the actual core, which would induce the errors to the simulation values of power distributions and hence to the burnup distributions. Therefore, a data-assimilation method has been proposed based on the three-dimensional variation (3DVAR) algorithm and the neutral network algorithm, aiming at reducing the errors of the burnup-distribution simulations with application of the power-distribution measurements. In our proposed method for the burnup distribution, the 3DVAR algorithm was applied to get the more-accurate burnup distribution, the neutral network algorithm was applied to obtain the complex relations between the burnup distributions and the power distributions which were essential for the 3DVAR. As method verification, the proposed method has been applied to a commercial PWR operated in China. It can be observed that through the data assimilation, the burnupdistribution errors can be reduced notably, as the maximum value of relative errors for power distribution can be notably reduced from 9.53% to 5.11%. Moreover, the key parameters including power-peak factors (Fq and FΔH) can also be improved. As concluded, the data-assimilation method based on the power-distribution measurements is efficient to improve the simulation accuracy of burnup distributions, and could further guarantee the economy and safety of PWR.